Acute transverse myelopathy complicating tetanus. Issue 669 (July 1981) - Bahemuka, M.
Abstract : A 12-year-old boy presented with typical features of short incubation tetanus. Spastic paraparesis with a mid-thoracic sensory level was present from the time of the initial examination. X-rays of the spine and lumbar myelogram were normal. The paraparesis improved rapidly and within a month the patient was free of neurological deficit. The case is possibly a rare example of tetanus involving the central nervous system other than the anterior horn cells.